2013
DOI: 10.4236/ojmi.2013.34022
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation of Sinusoids in Hematoxylin and Eosin Stained Liver Specimens Using an Orientation-Selective Filter

Abstract: The liver comprises cell layers of hepatocytes called trabeculae, which are separated by vascular sinusoids. Understanding the structure of hepatic trabeculae and liver sinusoids in hematoxylin and eosin (HE)-stained liver specimens is important for the differential diagnosis of liver diseases. In this study, we develop an approach to extracting liver sinusoids from HE-stained images. The proposed approach involves: 1) a new orientation-selective filter (OS filter) for edge enhancement and image denoising, 2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…In order to detect cervical cancer automatically with the help of screening tests. Among them one of the most important method is the segmentation of cell nuclei from the stained specimens [14]. However, isolated nuclei of the cells in high-quality acquisitions provide difficult tricks in the segmentation is more number of nuclei with various characteristics under occurring different acquisition conditions in good-resolution scans of the complete microscope slide [15].…”
Section: Introduction:-mentioning
confidence: 99%
“…In order to detect cervical cancer automatically with the help of screening tests. Among them one of the most important method is the segmentation of cell nuclei from the stained specimens [14]. However, isolated nuclei of the cells in high-quality acquisitions provide difficult tricks in the segmentation is more number of nuclei with various characteristics under occurring different acquisition conditions in good-resolution scans of the complete microscope slide [15].…”
Section: Introduction:-mentioning
confidence: 99%
“…We then apply the expectation-maximization (EM) algorithm to cluster bright pixels. filter is shown in Ishikawa et al, 15 where details of this step can be found.…”
Section: Sinusoid Extractionmentioning
confidence: 99%
“…Figure 3 shows an overview of the proposed method for the extraction and quantification of trabecular structure. We previously reported that trabeculae can be extracted using the structures outside liver cells (sinusoids and stromata), 14,15 which can be extracted more easily than liver cells themselves. The method introduced in this paper also follows the same approach: the sinusoid and stroma regions are segmented first, and then we extract the trabeculae regions by excluding those regions.…”
Section: Overview Of Hepatocellular Carcinomamentioning
confidence: 99%
See 2 more Smart Citations